PENGELOLAAN ARSIP DALAM MENINGKATKAN MUTU LAYANAN ADMINISTRASI DI MADRASAH ALIYAH NEGERI 1 MOJOKERTO - Fahmi ‘Asri; Heru Setiawan; Fahmi Siti Fatimah (STKIP Pesisir Selatan, 2026)
This study aims to analyze the archive management system and the quality of administrative services at MAN 1 Mojokerto in supporting the effectiveness and availability of school information. This study employs a qualitative approach with a case study design at MAN 1 Mojokerto. Data were collected through observation, interviews, and documentation techniques. Data analysis applied the Miles and Huberman model, encompassing data collection, data reduction, data display, and data verification, with validation conducted using source triangulation. The results show that archives at MAN 1 Mojokerto are managed in an integrated manner using a hybrid method (manual and digital). Although storage facilities still require improvement, archive personnel work efficiently and communicatively. In terms of service quality, the school has implemented an excellent time management, tracking, and document scheduling system, ensuring that urgent requests are handled quickly, accurately, and professionally. The novelty of this research lies in mapping the integration of manual-digital archive management that is directly synchronized with the administrative service time management system (on-time tracking system) within an Islamic Senior High School (Madrasah Aliyah) environment, a model that has not been widely investigated specifically in faith-based educational institutions.